How states promote cybersecurity for SMEs - Bustillos Ortega, Olda (2023)
Digitalization has increased the exponential use of information and communication technologies, consequently increasing the risk of cyberattacks, which threaten the global supply chain. Small and medium-sized companies and their ecosystems are the most affected by the lack of resources to protect their information assets' integrity, confidentiality, and availability. Increasing awareness of cybersecurity helps reinforce global immunity to cyberattacks. This article investigates how some countries' governments support the cybersecurity of small and medium-sized companies, highlights the best international practices, and identifies areas for improvement in capacity building for governments, policymakers, cyber security experts, and academics. Cybersecurity must be addressed with an interdisciplinary and holistic approach, with a multilateral application, since small and medium-sized companies need government and academic support to manage cyber risk and build a culture of cybersecurity.